The humanization of the process of educating logopedists (speech-language pathologists) at the university level - Szafrańska, Karina (My University, 2014)
Наголошується на необхідності гуманізації процесу навчання професійних логопедів (мовних дефектологів) на академічному рівні, розвитку їх професійних навичок і знань, а також їх відповідальності, поваги до потреб і прав інших осіб, чутливості, рефлексивності, а ще волі і готовності допомогти іншим людям у такій специфічній міждисциплінарній галузі, як логопедія. The article concerns the need of humanization of the process of educating professional logopedists (Language-Speech Pathologists) at an academic level - the development of their professional skills and knowledge, but also their responsibility, respect for the needs and rights of others, sensitivity, reflexiveness, and the will and readiness to help other people, in such a specific, interdisciplinary field as logopedics.
Keywords: логопед; speech therapist; логопед-дефектолог; speech-language pathologist; логопедія; speech therapy